2017
DOI: 10.2340/00015555-2657
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Myocardial Infarction in Patients with Psoriasis and Psoriatic Arthritis: A Nationwide Cohort Study

Abstract: Psoriasis has been associated with increased risk of myocardial infarction (MI) in some, but not all, studies. This study investigated the risk of MI in patients with psoriasis and psoriatic arthritis in Denmark. All residents aged ≥18 years from 1 January 2008 through 31 December 2012 were included. Adjusted hazard ratios (HRs) did not show an increased risk of MI in patients with mild psoriasis (HR 1.02; 95% confidence interval (95% CI) 0.96-1.09), whereas the risk was slightly increased in patients with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
3
34
0
3
Order By: Relevance
“…Similar to the present study, cross‐sectional data from Germany showed psoriasis to be associated with type 2 diabetes and myocardial infarction, but reported no association with hypertension, metabolic syndrome, angina pectoris or peripheral artery disease . Also within the same cohorts, separate studies report conflicting results where psoriasis is either related to an increased risk of myocardial infarction or not …”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Similar to the present study, cross‐sectional data from Germany showed psoriasis to be associated with type 2 diabetes and myocardial infarction, but reported no association with hypertension, metabolic syndrome, angina pectoris or peripheral artery disease . Also within the same cohorts, separate studies report conflicting results where psoriasis is either related to an increased risk of myocardial infarction or not …”
Section: Discussionsupporting
confidence: 73%
“…Systemic inflammation in psoriasis is put forward as an explanation of these associations, and aggressive screening of patients with psoriasis has been suggested . Study results are, however, not conclusive, and several population‐based studies show weak or no association between psoriasis and cardiovascular comorbidities . In addition, several of these studies are based on data from hospital registries, speciality clinics or visits to a general practitioner, where psoriasis patients are at increased risk of being screened for other diseases which thus might lead to detection bias .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to rheumatoid arthritis, 13 most but not all studies have associated psoriasis with an increased risk of CVD, 25, 1416 yet data suggest that classical CV risk factors alone do not fully capture this heightened risk, and systemic inflammation has been put forward as a potential explanation for the link between psoriasis and CVD. Along this line, inflammation is associated with impaired insulin sensitivity, carotid intima-media thickening, endothelial dysfunction, aortic stiffness, vascular inflammation, and coronary plaque burden and such CVD markers occur more frequently in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%